Peroxydisulphate-CuCl2 Utilizing in the Preparation of 3,4-Dihydro-2H-[2,2]-bifuranyl-5-one. - O. Mahmoodi, Nosrat; Dadvar, Poupak (Asian Journal of Chemistry, 2010)
The prefonned 4-(furan-2-yl) butyric acid (4) was converted in one pot to the corresponding 5-substituted γ-butyrolactone (8).